Observation scope and spatial coverage analysis for earth observation from a Moon-based platform. Issue 18 (17th September 2018) - Ye, Hanlin; Guo, Huadong; Liu, Guang; Ren, Yuanzhen
ABSTRACT: As a new concept platform for Earth observation, a Moon-based platform has the advantages of large-scale, constant and long-term dynamic Earth observations that can meet the needs of conducting systematic research on the Earth. However, a Moon-based platform has particular differences from space-borne and air-borne platforms because of its long distance from the Earth and the vast expanses of the Moon. In this article, we present three contributions. First, we propose a formula to describe the relative position of the Moon-based platform and Earth observation target. Second, we establish an observation geometry model and discuss three key observation parameters that are vital to the observation scope and coverage calculation. Third, a new observation scope and coverage analysis method is established in order to demonstrate that a suitable Moon-based Earth observation platform site can be located in the full observation region. We establish a geometric model for a Moon-based platform based on the Earth orientation parameters and Jet Propulsion Laboratory (JPL) ephemerides. Then, three key parameters including the visibility of the Earth from the Moon, nadir point, and Earth viewing angle are calculated using the proposed model. These parameters determine the observation scope and coverage of the Earth. The Earth-facing hemisphere of the Moon is divided into four regions, including the full observation region and the incomplete observation regions. Compared with the selenocentric case, during orbital periods, the maximum nadir point's latitudinal and longitudinal difference in terms of placing sensors on the Moon surface is about 0.3°, the maximum viewing angle difference of the Earth is about 0.005°, and the maximum angular difference of the Moon-based platform and the Sun is about 0.24°. Thus, the maximum coverage difference is about 0.1%, so that placing sensors on the full observation region would result in better Earth observation performance.